PENGEMBANGAN MODEL PENDUKUNG KEPUTUSAN DALAM MENENTUKAN KARTU SELULER SEBAGAI OPERATOR INTERNET BERDASARKAN PENDEKATAN ANALYTIC HIERARCHY PROCESS - Setiawan, Santoso (Jurnal Pilar Nusa Mandiri, 2012)
Fixed internet services available at home or at the company did not support its users to be online at any place. To subscribe to the internet the prospective users must go through lengthy requirements. Besides, with monthly costs that are relatively large, can sometimes be a burden the customers themselves. This thesis aims to overcome the above problems, so in the hope, things have been done on the internet can not be fixed, can be overcome. This thesis discusses the use of a cellular card as a medium for surfing. A number of cellular cards circulating in the market require a good selection method and structured so that later users can appropriate candidates choose mobile cards that match their needs. To be able to give appropriate guidance in the selection of cellular card, so in need of a method of choosing a good decision, one of which is Analytical Hierarchy Process (AHP) developed by Drs. Thomas L. Saaty of the Wharton School of Business. The end result of the AHP method is a proposed effective decision based on the processing of data obtained from respondents who had experienced or had to use mobile cards before. Processing the data in the auxiliary with Expert Choice, a decision support software, resulting in decisions that can get close to perfection. The conclusion that can be in the results of this study was to obtain a comparative result of the selection criteria to determine whether cellular card. In this study, which was used as reference criteria for comparison are Cellular Provider Card, Signal Strength, Rate of Saving. These three criteria for the moment it is enough to be able to represent the respondent's interest in choosing a cellular card for Internet operators make.